MATERNAL-FETAL TOLERANCE AS A MANIFESTATION OF REGULATORY CONTINUUM AND PLASTICITY OF THEIR IMMUNE SYSTEMS (in memory of I.P. Ashmarin) - E. P. Kharchenko (Медицинская иммунология)
Abstract. Relations of immune tolerance between mother and fetus are considered in view of a common regulatory continuum which is formed under the influence of a growing fetus. To explain such an immune tolerance, a notion of immune system plasticity is introduced, as an analogue to the nervous system plasticity, which develops in response to a continuum of changes occurring in fetal and maternal organisms during the nine months of pregnancy. The immune system plasticity in females is supposed to be among possible factors causing collisions upon conception and in the course of pregnancy. (Med. Immunol., 2011, vol. 13, N 2-3, pp 121-132)